2020
DOI: 10.1097/brs.0000000000003917
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy X-ray Absorptiometry Does Not Represent Bone Structure in Patients with Osteoporosis

Abstract: Study Design Prospective cross-sectional exploratory study. Objective To evaluate the correlation between in vivo lumbar dual-energy x-ray absorptiometry (DXA) and parameters of bone architecture in micro–computed tomography (micro-CT) in patients with osteoporosis. Summary of Background Data DXA is the current diagnostic standard for evaluating osteoporosis. However, there are various concerns regarding its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, it should be considered that the T-score sometimes shows discordance with osteoporotic fracture risk. Degenerated lumbar spine showed uncertainty for BMD measurement for aging [ 42 ]. Measurement of bone density can be affected by calcifying structures around the spine, which are the anterior and posterior longitudinal ligaments, ligament flavum, aorta, and interspinous ligament [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be considered that the T-score sometimes shows discordance with osteoporotic fracture risk. Degenerated lumbar spine showed uncertainty for BMD measurement for aging [ 42 ]. Measurement of bone density can be affected by calcifying structures around the spine, which are the anterior and posterior longitudinal ligaments, ligament flavum, aorta, and interspinous ligament [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Degenerated lumbar spine showed uncertainty for BMD measurement for aging [ 42 ]. Measurement of bone density can be affected by calcifying structures around the spine, which are the anterior and posterior longitudinal ligaments, ligament flavum, aorta, and interspinous ligament [ 43 , 44 ]. Therefore, the prediction of fracture risk through only BMD is a challenge concerning the degenerative spine, especially in those who cannot use hip BMD due to history of hip fracture or surgery, and attempts are being made to compensate for this problem with a new method called the trabecular bone score to measure the microstructure of bones [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other parameters like bone microarchitecture and bone composition cannot be predicted with the current gold standard for evaluating BMD and DEXA [ 17 ]. Pumberger et al demonstrated that DEXA measurements of the spine do not properly represent the microstructure of the vertebral body and are therefore not a reliable tool to determine bone quality in the spine [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, areal bone mineral density, quantifies primarily the quantity of bone and does not capture the other factors that contribute to bone integrity, such as microarchitecture, bone remodeling, and collagen properties. [15][16][17] Bone collagen is subject to posttranslational modifications, such as non-enzymatic collagen cross-linking, resulting in advanced glycation endproducts (AGEs). 17 The accumulation of AGEs is associated with impaired mechanical bone properties indicative of poor bone quality.…”
mentioning
confidence: 99%
“…Osteoporosis is commonly diagnosed using dual-energy x-ray absorptiometry derived from areal bone mineral density. However, areal bone mineral density, quantifies primarily the quantity of bone and does not capture the other factors that contribute to bone integrity, such as microarchitecture, bone remodeling, and collagen properties 15–17 . Bone collagen is subject to posttranslational modifications, such as non-enzymatic collagen cross-linking, resulting in advanced glycation endproducts (AGEs) 17 .…”
mentioning
confidence: 99%